The politics of Armenian migration to North America, 1885-1915 : sojourners, smugglers and dubious citizens - Gutman, David (Edinburgh studies on the Ottoman Empire., 2019)
This book tells the story of Armenian migration to North America in the late Ottoman period, and Istanbul's efforts to prevent it.